PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM PADA ANGGOTA ORKI TANGERANG SELATAN - Agus Sudarsono; Abdul Khoir; Suhandi (Abdi Jurnal Publikasi, 2025)
The purpose of this community service program is to improve members' skills in utilizing digital marketing to increase sales of MSME products. The method of implementation is counseling on the use of digital marketing as an alternative means of marketing MSME products. The partners for this program are community-based organizations engaged in sports and fitness in South Tangerang. The evaluation instrument used pre-tests and post-tests, which were then analyzed descriptively. The results of this program indicate a 65% increase in members' knowledge of digital marketing for cooperatives and a 35% increase in their knowledge of the stages of using digital marketing to establish a cooperative. Furthermore, participants are motivated to improve their family's income by increasing sales of their MSME products through digital marketing.